LANDASAN FORMIL DAN MATERIIL KONSTITUSIONAL PERATURAN PERUNDANG-UNDANGAN - Aziz, Machmud (Direktorat Jenderal Peraturan Perundang-undang, Kementerian Hukum dan Hak Asasi Manusia, 2009)
A real and good understanding of formal and material constitution basis oflegislations is conditio sine quanon to the legislative drafters in order theirlegislation product that they made not easily cancelled in judicial review byThe Constitutional Courts (UU) or by The Appellate Courts (any legislationsbelow UU).